RNF213 regulates blood‒brain barrier integrity by targeting TRAF3 for type I interferon activation during A. baumannii infection. - Yanfeng Li; Qingqing Xie; Luyu Yang; Qian Jiang; Zhiping Liu; Chengjiang Gao; Xiaopeng Qi; Tao Xu (PLoS Pathogens, 2025)
RNF213 is the first identified susceptibility gene for moyamoya disease, and the encoded protein was recently recognized as a key antimicrobial protein. However, the function of RNF213 in host defense against brain infection remains unclear. Here, we show that increased expression of Rnf213 is significantly regulated by interferon alpha/beta receptor (IFNAR) signaling during bacterial infection and ligand stimulation. RNF213 deficiency impairs type I interferon (IFN-I) production and decreases the expression of interferon-stimulated genes (ISGs) in response to IFN-β stimulation and Acinetobacter baumannii infection. Mechanistically, RNF213 interacts with TRAF3 and mediates the K27-linked polyubiquitination of TRAF3 at K160. RNF213 regulates the expression of the endothelial tight junction-related genes Claudin-5, Occludin, and Pecam1 via IFN-I signaling. Furthermore, RNF213 deficiency in nonimmune cells increases blood‒brain barrier (BBB) disruption and the bacterial load in the brain parenchyma in response to A. baumannii infection due to impaired IFN-I signaling. Thus, RNF213 mediates BBB integrity by targeting TRAF3 for the regulation of IFN-I signaling against bacterial brain infection. Our study principally provides a deeper understanding of the function of RNF213 and reveals potential therapeutic targets against bacterial brain infection and moyamoya disease.